Mitochondrial DNA maintenance disorders in 102 patients from different parts of Russia: Mutational spectrum and phenotypes - Bychkov, I.O.; Itkis, Y.S.; Tsygankova, P.G.; Krylova, T.D.; Mikhaylova, S.V.; Klyushnikov, S.A.; Pechatnikova, N.L.; Degtyareva, A.V.; Nikolaeva, E.A.; Seliverstov, Y.A.; Kurbatov, S.A.; Dadali, E.L.; et al. (Mitochondrion, 2021)
•The largest Russian cohort of patients with mtDNA maintenance disorders was analysed.•Some peculiar features of the mutational spectra for the TWNK and the DGUOK genes were found.•High frequency of c.2243G > C mutation in the POLG gene was established. Currently, pathogenic variants in more than 25 nuclear genes, involved in mtDNA maintenance, are associated with human disorders. mtDNA maintenance disorders manifest with a wide range of phenotypes, from severe infantile-onset forms of myocerebrohepatopathy to late-onset forms of myopathies, chronic progressive external ophthalmoplegia, and parkinsonism. This study represents the results of molecular genetic analysis and phenotypes of 102 probands with mtDNA maintenance disorders. So far, this is the largest Russian cohort for this group of diseases. Mutations were identified in 10 mtDNA maintenance genes: POLG (n = 59), DGUOK (n = 14), TWNK (n = 14), TK2 (n = 8), MPV17 (n = 2), OPA3 (n = 1), FBXL4 (n = 1), RRM2B (n = 1), SUCLG1 (n = 1) and TYMP (n = 1). We review a mutation spectrum for the DGUOK and TWNK genes, that can be specific for the Russian population. In 34 patients we measured the blood mtDNA copy number and showed its significant reduction. Novel variants were found in 41 cases, which significantly expands the mutational landscape of mtDNA maintenance disorders.